The Effectiveness of The Powerpoint Assisted SQ4R Model on Reading Skills In Class V Students - Selfie, Selfie; Hartati, Hartati (Elementary School Teacher, 2021)
Based on the results of interviews, observations, and documentation at Ki Hajar Dewantara Cluster Elementary School, Kebumen, it was found that the reading comprehension learning had not been carried out optimally. The research objective was to test the effectiveness of Survey, Question, Read, Recite, Review, Reflect learning model assisted by powerpoint on reading comprehension skills of the fifth grade students at Ki Hajar Dewantara Cluster Elementary School. This research used quantitative approach, Quasi-experimental type with nonequivalent control group design. The data collection techniques used observation, documentation, and tests. The results of the t test using the Independent Sample T-Test showed the value (2-tailed) 0.05, the column (2-tailed) of 0.002 was smaller than 0. 05 which means that there was a significant difference between the posttest results of the experimental class and the control class. The N-Gain calculation of the control class included in low criteria and the experimental class included in moderate criteria. In conclusion, the powerpoint assisted SQ4R learning model was more effective than the lecture and group discussion methods on reading comprehension skills in the fifth grade students at Ki Hajar Dewantara Cluster Elementary School.Keywords: SQ4R, reading comprehension, powerpoint